Licenciatura em Espanhol: repercussões do conhecimento específico nos processos formativos docentes - Stahl, Luana Rosalie (2013)
The following study is attached to the project The movements of higher teaching practice: possible constructions in different areas of knowledge from the Group GTFORMA, and it is inserted in the fieldwork Formation, Knowledge and Professional Development, from the Post-Graduation Program in Education at Federal University of Santa Maria (UFSM). The research is associated with the investigation field of university pedagogy and formation of teachers; its investigative context is the Graduation in Spanish Language and Literature Teaching at UFSM. We established as a main objective to investigate what are the effects of the specific area of knowledge in the formation process of teachers of Spanish. In that way, we tried to comprehend how the specific area of knowledge engenders in the way the teacher conducts his own formation process and also of his students, it also leads to infer the relation between the way the teachers articulate the knowledge that belongs to the specific area together with the formation of future teachers to the basic education. In order to achieve these objectives, we used the narratives from six professors that work with formation. This research is justified by the necessity of studies that have as their focus the problematic of the specific knowledge area and the articulation with pedagogical knowledge in the processes of teaching formation, trying to comprehend how the formation of future teachers to basic education happens. The methodological option of this research is the qualitative one, having a narrative status (BOLÍVAR, DOMINGO e FERNÁNDEZ, 2001; CONNELLY e CLANDININ, 1995; HUBERMAN, 1998; MCEVAN, 1998). In relation to the analytical interpretation, we chose the discursive method of textual analysis (BAUER e GASKELL, 2004; MORAES e GALIAZZI, 2007). The analysis of the narrative interviews enables the development of three categories: levels of awareness about the formation role, dealing with different levels of comprehension of the role of forming teachers that suffer interference from the elements such as the notion that the teacher builds about the student in the graduation course, the concepts of teaching and the trajectory of formation from these professors; the pedagogical loneliness understood as the feeling that emerges from the weak identity of the formative group, the curricular structure of the teaching graduation and the absence of articulation between the concepts of the area and other related areas and the relevance of specific knowledge and the meaning of pedagogical knowledge in the formation of teachers apprehended based on the comprehension that the formation of teachers lead their practice in the specific area though they understand that there are different levels/types of knowledge (scientific, academic, school) revealing notions of didactic transposition and identification of the movement of articulation of the specific knowledge to the formation of teachers. Such results indicate a university teaching in the area of Spanish Language built based on the specific knowledge, on the pedagogical loneliness and on the course searching from a higher articulation with the pedagogical formation that seems to be constrained to the other two categories.